European Scenarios of CO2 Infrastructure Investment until 2050 - Pao-Yu Oei; Roman Mendelevitch (The Energy Journal, 2016)
Based on a review of the current state of the Carbon Capture, Transport and Storage (CCTS) technology, this paper analyzes the layout and costs of a potential CO2 infrastructure in Europe at the horizon of 2050. We apply the mixed-integer model CCTS-Mod to compute a CCTS infrastructure network for Europe, examining the effects of different CO2 price paths with different regional foci. Scenarios assuming low CO2 certificate prices lead to hardly any CCTS development in Europe. The iron and steel sector starts deployment once the CO2 certificate prices exceed 50 exteuro /tCO2. The cement sector starts investing at a threshold of 75 exteuro /tCO2, followed by the electricity sector when prices exceed 100 exteuro/tCO2. The degree of CCTS deployment is found to be more sensitive to variable costs of CO2 capture than to investment costs. Additional revenues generated from utilizing CO2 for enhanced oil recovery (CO2-EOR) in the North Sea would lead to an earlier adoption of CCTS, independent of the CO2 certificate price; this case may become especially relevant for the UK, Norway and the Netherlands. However, scattered CCTS deployment increases unit cost of transport and storage infrastructure by 30% or more.
Additional information: This is the preprint of an article published in Energy Journal , available online at: https://doi.org/10.5547/01956574.37.SI3.poei
Keywords: 330; CCS; CCTS; CO2 emissions; Scenario analysis; Infrastructure; Modeling; EOR